2020
DOI: 10.1155/2020/7372868
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis Analysis of Liver Cirrhosis with Acute Variceal Bleeding and Validation of Current Prognostic Models: A Large Scale Retrospective Cohort Study

Abstract: Background. Acute variceal bleeding is a major cause of death in liver cirrhosis. This large scale retrospective cohort study aims to analyze the prognosis of patients with cirrhosis and acute variceal bleeding and to validate the current prognostic models. Methods. Patients with cirrhosis and acute variceal bleeding were enrolled from Jan 2019 to March 2020. The independent prognostic factors for in-hospital death were identified by logistic regression analyses. Area under curves (AUCs) was compared among Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…And one study was excluded because the UGIB was not confirmed by an endoscope. At last, 28 articles were included in the study [ 13 , 14 , 19–44 ] (see Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And one study was excluded because the UGIB was not confirmed by an endoscope. At last, 28 articles were included in the study [ 13 , 14 , 19–44 ] (see Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly used to estimate mortality in patients who had a transjugular intrahepatic portosystemic shunt (TIPS) procedure [ 11 ] and prioritize for receipt of a liver transplant [ 12 ]. Previous studies had reported the two staging systems’ predictive abilities in AVB patients’ outcomes, but which could reflect the prognosis more accurately remained controversial [ 13 , 14 ]. We aim to conduct a systematic review of the predictive value of GBS, AIMS65, Rockall (clinical Rockall score and full Rockall score), CTP and MELD in risking stratify AVB patients for mortality and rebleeding within three months after the initial bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the rates of rebleeding and mortality at 6 weeks were lower than those reported in previous studies [4,17]. This nding could be attributed to the following reasons: rst, new medications and techniques have been developed recently to effectively decrease PH and prevent rebleeding; second and more importantly, it was the rst EVL for our patients; more than half of our patients had never had a bleeding before and 90% of the patients were having a Child-Pugh class A or B; third, patients with hepatocellular carcinoma, which has been reported to be associated with the prognosis of patients who have experienced an episode of variceal bleeding[26, [43][44][45]were excluded from our study. Rebleeding occurred in 21.10% and 20.18% of patients with PVT and CCG, respectively, at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…The MELD-Na and CAGIB scores were calculated using relevant data in the following formula: MELD-Na = 3.8 × log e (bilirubin [mg/dl]) + 11.2 × log e (INR) + 9.6 × log e (creatinine [mg/dl]) + 6.4 × (etiology: 0 for cholestasis or alcohol, otherwise 1) + 1.59 × [135 – sodium (mmol/L)], and CAGIB score = DB(1 for yes, 0 for no) × 1.040 + HCC(1 for yes, 0 for no) × 0.974 + bilirubin (μmoI/L) × 0.005 – albumin (g/L) × 0.091 + ALT (U/L) × 0.001 + creatinine (μmoI/L) × 0.012 – 3.964 ( 21 ).…”
Section: Methodsmentioning
confidence: 99%